Numerical modeling of multiphase flow inside aeromixture channel and low emission burner of boiler OB-650 - Mešić, Amel; Delić, Izudin; Ganibegović, Nedim (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Determination of multiphase flow inside PC boiler plant is of particular importance for the process control of the boiler and its efficient operation. Nowadays numerical modeling is used as an advanced tool in improvement of this or similar process. Separation of coal particle in aero-mixture channel, after pulverization, represent an important process which has a big effect on boiler efficiency, and its determination represents an important step. In this paper, numerical modeling of multiphase flow inside aero-mixture channel and low emission burner of boiler OB-650 are exposed in several steps from 3D modeling, discretization of fluid domain, setting the physical and mathematical model to validation of same model. Main goals of the same process is to obtain valid numerical model of observed problematic, that will give us data about model parameters that can be used for modeling of the same process with different inlet boundary conditions, and also to obtain appropriate specific process parameters that can be used for rising of level of efficiency and utility of boiler plant in some steady operating modes.